2016
DOI: 10.1097/brs.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Implant Failure of Titanium Versus Cobalt-Chromium Growing Rods in Early-onset Scoliosis

Abstract: Rod fractures occurred more commonly with titanium rods and connector fractures with cobalt-chromium rods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Failure was not associated with the degree of curve, length of time, or age of the child. The overall mechanical failure rate (all causes) in our cohort was 50%, which agrees with the failure rate of TGR systems that has been previously reported (approximately 40%–70%) [ 3 , 14 - 17 ]. The patient’s size, contouring of rods, actuator magnets that are too close to one another, and actuator magnets too close to the apex of the curve are factors associated with the failure of magnetically controlled lengthening devices [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Failure was not associated with the degree of curve, length of time, or age of the child. The overall mechanical failure rate (all causes) in our cohort was 50%, which agrees with the failure rate of TGR systems that has been previously reported (approximately 40%–70%) [ 3 , 14 - 17 ]. The patient’s size, contouring of rods, actuator magnets that are too close to one another, and actuator magnets too close to the apex of the curve are factors associated with the failure of magnetically controlled lengthening devices [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…We distinguish failure in which a further MCGR system is inserted from failure that is treated by final spinal fusion. The exact conditions for failure may become more obvious over time, and there certainly appears to be some correlation in the literature with increasing body habitus, age of the child, and orientation of magnets [ 14 , 18 ]. However, we are hesitant to label cases as failures if the children subsequently went on to be treated with final spinal fusion, which would be appropriate for the child in any event.…”
Section: Discussionmentioning
confidence: 99%
“…Rod fracture (RF) is the most common mode of device failure following complex spinal reconstruction. 18 , 19 The longitudinal rods must provide adequate support to the instrumented spine as fusion occurs in the affected areas over the course of weeks to months. Failure at the level of these longitudinal rods may occur due to a sustained increase in motion across the fusion levels as result of delayed union or pseudoarthrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture failure is not rare in orthopedic (long bone [7] , [8] and spine [9] , [10] ) and dental implants [11] , [12] . Unlike its counterpart, the cranioplasty prosthesis is not under weight-loading conditions (as orthopedic implants) or bearing obvious extra force (as dental implants).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated several contributors for implant fracture: (1) inappropriate implant material [8] , (2) bad implant designs [13] , (3) inappropriate fixator selection [10] , [14] , (4) inappropriate surgical technique [9] , (5) and (6) biomechanical overload [15] , [16] . These factors are deleterious for implants fatigue resistance, which eventually lead to fracture.…”
Section: Discussionmentioning
confidence: 99%